Morphological, Sedimentary and Chemical Changes in Beaches at Harmul, Majees and Zafaran, Oman - Abdullah Al-Shuely, Wahid Mohammed (2011)
This thesis examines the morphological changes of three beaches close to Sohar Industrial Are (SIA), a newly developed industrial area north of the Batinah Region in Oman. The construction work on the port breakwaters started in 1999 and was complete 2002. Three sites were selected for this project: Harmul, located north of SIA, Majees south of SIA, and Zafaran, about nine kilometers south of Majees. The main purpose of this thesis is study the changes likely to occur on beaches north and south of SIA. Major focus will be on beach profiles and sediment characterization with respect to mean, sorting, skewness, particle distribution, particle density, and bulk density. Sediment samples were also analyzed for 11 heavy metals including: vanadium (V), chromium (Cr), manganese (Mn), nickel (Ni), copper (Cu), selenium (Se), mercury (Hg), cadmium (Cd), lead (Pb), zinc (Zn) and arsenic (As) using microwave digestion followed by Inductively Coupled Plasma-Mass Spectrometry (ICP-MS). No previous study had been conducted on these beaches. Although a comprehensive master plan was developed for Sohar industrial area, which included a strategic environmental impact assessment, the master plan contained little information on physical and chemical characteristics of beaches north and south of the industrial area. A total of 252 surface sediment samples were collected in four site visits over 12 months: November 2005, February 2006, June 2006, and November 2006. Each site was divided into seven stations. Three sediment samples were collected from each station from highwater, intertidal and surf zones. Beach profiles showed little seasonal variations in 67% of profiles surveyed and about 24% showed big seasonal variations. Almost 81% of all samples were fine sand and 19% were medium sand. Moderately sorted sediments represented 56% of all samples, whereas 22% of samples were moderately well sorted and 22% were poorly sorted. Half of the samples were near symmetrical, whereas 39% of the samples were coarsely skewed and 11% were fine skewed. Sediment trend analysis showed that wadis were the main source of sediments in the study area. June 2006 samples had a higher particle density than November 2006 samples. There was no significant difference in sediment bulk density between the three sites for June 2006 samples (p = 0.203) but significant difference was found in November 2006 samples (p=0.015). The concentrations of chromium, manganese, and vanadium were higher in Harmul than Majees and Zafaran. Arsenic concentration was generally low except in few stations. It is concluded that the impacts of Sohar industrial area on these beaches are still not apparent but more research is needed to identify any impacts in its early stage and set prevention and mitigation measure programs to reduce the anticipated impacts of Sohar industrial area on the beach environment.